2013
DOI: 10.1074/jbc.c112.421768
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of Recombinant Human Lysyl Oxidase-like 2 (rhLOXL2) Secreted from Drosophila S2 Cells*

Abstract: Background: hLOXL2 induces metastasis/invasion of breast cancer cells. Results:The N-glycans and lysine tyrosylquinone (LTQ) cofactor of rhLOXL2 are determined. Conclusion: N-Glycans are essential for proper folding and secretion of hLOXL2 from S2 cells. Significance: This is the first determination of 1) LTQ in the hLOX family of proteins and 2) N-glycosylation in the LOX catalytic domain in the LOX family of proteins.Human lysyl oxidase-like 2 (hLOXL2) is highly up-regulated in metastatic breast cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 31 publications
1
50
1
Order By: Relevance
“…We previously confirmed by mass spectrometry that Lys-653 and Tyr-689 are the precursor residues for the LTQ cofactor in LOXL2 (19). Biogenesis of the LTQ cofactor is proposed to be autocatalytic, requiring only Cu 2ϩ and molecular oxygen (3,29).…”
Section: Selection Of Mcf-7 Cells Stably Expressing Catalytically Incmentioning
confidence: 82%
See 3 more Smart Citations
“…We previously confirmed by mass spectrometry that Lys-653 and Tyr-689 are the precursor residues for the LTQ cofactor in LOXL2 (19). Biogenesis of the LTQ cofactor is proposed to be autocatalytic, requiring only Cu 2ϩ and molecular oxygen (3,29).…”
Section: Selection Of Mcf-7 Cells Stably Expressing Catalytically Incmentioning
confidence: 82%
“…These results confirm that the N-linked glycans at Asn-455 and Asn-644 are independently essential for secretion from breast cancer cells as disruption of N-glycosylation at either site results in the loss of the N-linked glycan at the other site and total inhibition of secretion, a phenomenon for which there is some precedent (23,24). Interestingly, the N455Q and N644Q LOXL2s produced in MCF-7 cells were soluble, in contrast to the corresponding truncated forms of recombinant LOXL2 expressed in S2 cells, which were detected in minute quantities only in the insoluble S2 cell lysate, implicating rapid endoplasmic reticulum-associated degradation of nonglycosylated LOXL2 (19). The stark difference suggests that in MCF-7 cells, the N-linked glycans are essential neither for the folding nor for the stability of LOXL2.…”
Section: Selection Of Mcf-7 Cells Stably Expressing Catalyticallymentioning
confidence: 87%
See 2 more Smart Citations
“…We have worked to define the posttranslational modifications of LOXL2 and their impact on LOXL2 subcellular localization, enzyme activity and biological functions. We recently reported that N-glycosylation, but not LTQ cofactor formation, is essential for LOXL2 secretion (24)(25)(26). Here, we focused on rLOXL2 secreted from HEK293 cells to define the mode of proteolytic processing of LOXL2 and assess the importance of the processing on the LOX amine oxidase activity of LOXL2 in vitro.…”
mentioning
confidence: 99%